Diversidade e distribuição de larvas de odonata em múltiplas escalas espaciais : influências regionais e locais - Uhde, Vera (2012)
Stream systems incorporate different spatial scales in successive levels. The comprehension of this hierarchy allows more effective management and conservation measures. Many factors are correlated in space and act simultaneously over the aquatic fauna. Because of this complexity, few studies have demonstrated the importance of factors that regulate local and regional richness of aquatic communities. On this manner, our first objective is to identify the main spatial scale which contributes to the total diversity of Odonata larvae. The second objective is to determine how environmental factors on both regional (soil use and vegetation) and local (substracts, water speed and riparian forest) scales influence the species distribution. The collecting took place in the Alto Paraguai basin plateau and the sampling delineation included four hierarchical scales: sub-basins, micro-basins; streams and micro-habitats. A total of 920 larvae of Odonata were collected, distributed in 9 families and 29 genera. The result revealed that the microbasins spatial scale presented the highest diversity and plays a fundamental role in structuring the species composition of this region. Soil use with pastures and regions with forest were the main environmental factors of regional scale which determined odonate larvae distribution, while locally, the larvae depend on the different kinds of substrate. Our results emphasize the need of studies that recognize the spatial level of micro-basins to better comprehend the geographical variation of freshwater biodiversity. Future planning need to associate species richness to local scale, but specially, large scale factors, in order to recognize the presence of a spatially structured environmental variance.